The Probiotic Kluyveromyces lactis JSA 18 Alleviates Obesity and Hyperlipidemia in High-Fat Diet C57BL/6J Mice - Yingxiang Hong; Guodong Song; Xiaoqian Feng; Jialei Niu; Lu Wang; Caini Yang; Xuegang Luo; Sa Zhou; Wenjian Ma (Foods, 2024)
Obesity poses a significant threat to various health conditions such as heart diseases, diabetes, high blood pressure, and heart attack, with the gut microbiota playing a crucial role in maintaining the body’s energy balance. We identified a novel probiotic fungal strain, Kluyveromyces lactis JSA 18 (K. lactis), which was isolated from yak milk and was found to possess anti-obesity properties. Additionally, Lactobacillus plantarum CGMCC 8198 (LP8198) from our previous study was also included to evaluate its anti-obesity properties. The findings indicated that K. lactis caused a notable reduction in weight gain, liver and fat indexes, and hyperlipidemia in mice fed a high-fat diet (HFD). Administering K. lactis and LP8198 to mice on a high-fat diet resulted in a reduction of serum triglyceride levels. Furthermore, the supplements reduced ALT and AST activity, and inhibited the production of inflammatory cytokines such as TNF-α and IL-1β. In addition, lipid metabolism was enhanced by the downregulation of ACC1, PPAR-γ, SREBP-1, and Fasn. Moreover, this study found that K. lactis and LP8198 have little effect on gut bacteria. Additionally, K. lactis partially influenced intestinal fungi, while LP8198 had a minor influence on gut mycobiota. The main goal of this research was to show how effective K. lactis can be as a probiotic in combating obesity.